BEST PRACTICE PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS CERPEN - Tengku Nurmilawati (sarasvati, 2022)
This best practice activity was carried out at SMP Negeri 1 Pelalawan, which is located at Jalan Tugu Kemerdekaan 05 Pelalawan, Pelalawan Village, Pelalawan Regency, Riau Province. The problem encountered was the low ability of class IX students of SMP Negeri 1 Pelalawan, Pelalawan District, in writing short stories. The purpose of this best practice activity is to improve students’ ability to write short stories. The model used is Problem Based Learning (PBL) using serial image media. The results of the best practice activities showed an increase in the ability of class IX students of SMP Negeri 1 Pelalawan, Pelalawan District, in writing short stories.